U.S. Prison Seminaries: Structural Charity, Religious Establishment, and Neoliberal Corrections - Hallett, Michael A. (The prison journal, 2019)
Using archival and site-based research, this article explores operational practices at six U.S. prison seminary programs regarding concepts of religious establishment. Further highlighted is a shift toward faith-based volunteerism as a “structural charity” in correctional budgeting. While religious programs offer powerfully transformative access to social capital for many inmates, the recent insertion of Christian “seminaries” into U.S. prisons arguably fosters religious establishment in four key areas: a lack of state neutrality toward religion, excessive state entanglement with religious service providers, inadequate solicitation of alternative programming, and a de facto measure of coercion in delivery of services.